2013
DOI: 10.2174/09298673113209990155
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Flavonoids in Central Nervous System Disorders

Abstract: Neurodegenerative, neurological and psychiatric diseases are a group of pathologies with huge social and economic impacts. Since brain disorders continue to be pathological conditions for which corrective surgery cannot be widely used, treatments are based on drugs that only alleviate the symptoms. Despite all efforts in finding more efficient therapeutic agents, the requirement for neuroprotective drugs able to cross the blood-brain barrier (BBB) has been a hard challenge to overcome. Flavonoids are known by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 0 publications
2
56
0
1
Order By: Relevance
“…Treatment with co-ultraPEALut at the dose of 1 mg/kg (PEA/luteolin in a 10:1 mass ratio) reduced motor disturbance after SCI more effectively than treatment with PEA and luteolin (Lut) administered alone or with PEA (0.9 mg/kg) + Lut (0.1 mg/kg) administered as combination therapy. flavonoids, polyphenolic phytochemicals with potent antioxidant capacity, exhibit well-described neuroprotective/antiinflammatory actions [55]. Among the family of flavonoids, luteolin (3′,4′,5,7-tetrahydroxyflavone) is claimed to possess memory-improving [56] and anxiolytic [57] effects.…”
Section: Resolution Of Inflammation: Capitalizing On Nature's Defensementioning
confidence: 99%
“…Treatment with co-ultraPEALut at the dose of 1 mg/kg (PEA/luteolin in a 10:1 mass ratio) reduced motor disturbance after SCI more effectively than treatment with PEA and luteolin (Lut) administered alone or with PEA (0.9 mg/kg) + Lut (0.1 mg/kg) administered as combination therapy. flavonoids, polyphenolic phytochemicals with potent antioxidant capacity, exhibit well-described neuroprotective/antiinflammatory actions [55]. Among the family of flavonoids, luteolin (3′,4′,5,7-tetrahydroxyflavone) is claimed to possess memory-improving [56] and anxiolytic [57] effects.…”
Section: Resolution Of Inflammation: Capitalizing On Nature's Defensementioning
confidence: 99%
“…Although modern treatments are effective at managing the early motor symptoms of the disease [76], and surgery and deep-brain stimulation can be of use when drugs do not suffice to control symptoms [77], as there is currently no cure for PD. Interestingly, a diet enriched in polyphenol compounds has shown some efficacy in alleviating the symptoms of PD [78]. For example, in MPTP-injected mice, a toxin known to induce neuronal death, resveratrol was able to prevent MPTP-induced depletion of striatal dopamine, and to maintain striatal tyrosine hydroxylase protein levels, two neuropathological markers observed in PD patients [78,79].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Interestingly, a diet enriched in polyphenol compounds has shown some efficacy in alleviating the symptoms of PD [78]. For example, in MPTP-injected mice, a toxin known to induce neuronal death, resveratrol was able to prevent MPTP-induced depletion of striatal dopamine, and to maintain striatal tyrosine hydroxylase protein levels, two neuropathological markers observed in PD patients [78,79].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…A recent clinical trial reported statistically significant benefits of a luteolin-containing dietary supplement in children with autism (Taliou et al, 2013), many of whom have "allergic-like" symptoms (Theoharides, 2013b), which implicates MC activation (Theoharides et al, 2012b). In fact, flavonoids have recently been discussed as a possible treatment of central nervous system disorders (Jager and Saaby, 2011; Grosso et al, 2013).…”
Section: Treatmentmentioning
confidence: 99%